2010
DOI: 10.2746/042516406778400655
|View full text |Cite
|
Sign up to set email alerts
|

Racing performance after arthroscopic removal of apical sesamoid fracture fragments in Thoroughbred horses age ≥ 2 years: 84 cases (1989-2002)

Abstract: Summary Reasons for performing study: Studies have shown that surgical removal of apical fracture fragments in Standardbred racehorses carries the best prognosis for return to racing performance, but there are no reports involving mature Thoroughbred (TB) racehorses. Objectives: To describe the incidence of apical proximal sesamoid fractures in TB racehorses and determine probability and quality of racing performance after arthroscopic removal of such fractures in TB racehorses age ≥2 years. Methods: Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 7 publications
2
34
1
Order By: Relevance
“…Such evidence contrasts with the results of GOMES & ALVARENGA (1998) who showed that even with a mean of 161 lay-up days (considered extensive in the present study), later athletic performance of the evaluated horses was inferior to previous performance. Similar results were reported by SCHINABEL et al (2006) who found that even with a mean of 368 rehabilitation days, the majority of the evaluated animals did not show improvement in their later performances. One important reason for the discrepancy in the results could have been that the above cited authors evaluated the recovery from arthroscopic removal of fracture fragments whose challenge was perhaps greater than that faced by the animals of the present study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Such evidence contrasts with the results of GOMES & ALVARENGA (1998) who showed that even with a mean of 161 lay-up days (considered extensive in the present study), later athletic performance of the evaluated horses was inferior to previous performance. Similar results were reported by SCHINABEL et al (2006) who found that even with a mean of 368 rehabilitation days, the majority of the evaluated animals did not show improvement in their later performances. One important reason for the discrepancy in the results could have been that the above cited authors evaluated the recovery from arthroscopic removal of fracture fragments whose challenge was perhaps greater than that faced by the animals of the present study.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, GOMES & ALVARENGA (1998) and SCHINABEL et al (2006) assessed rehabilitation time following arthroscopic surgery using the number of days until the fi rst race without a temporal scale of categories. Regarding performance evaluation, GOMES & ALVARENGA (1998) determined only the percentage of classifi cations and total number of previous and later races, and did not make clear the categorization of the type of race on which the evaluation was based.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Schnabel et al (2006Schnabel et al ( & 2007 reported the results of arthroscopic removal of apical sesamoid fracture fragments in Thoroughbred racehorses. Of Thoroughbreds 31 out of 38 (82%) ran at the same or at an improved level (Schnabel et al, 2006).…”
Section: Removal Of Fragments From the Proximal Sesamoid Bonesmentioning
confidence: 99%
“…Of Thoroughbreds 31 out of 38 (82%) ran at the same or at an improved level (Schnabel et al, 2006). Horses with medial proximal sesamoid bone fractures were less likely (26 out of 40; 65%) to race postoperatively than those with lateral fractures (35 out of 39; 90%).…”
Section: Removal Of Fragments From the Proximal Sesamoid Bonesmentioning
confidence: 99%
See 1 more Smart Citation